Some Medieval Epistolic Language Features in the Latin Letters of Vytautas the Great - Keršienė, Dovilė (Literatūra, 2017)
The main challenge for anyone who attempts to research or translate medieval epistolary texts is the complexity and specifics of the epistola regia (royal letters) genre. The present article analyses letters written by Vytautas the Great, Grand Duke of Lithuania (1350–1430), focusing on the translation of said letters with regard to special aspects concerning the difficulties faced by the translator. There are no scientific papers which focus on the difficulties in translating Vytautas’ letters from Latin. From the nearly 450 surviving letters of the Grand Duke, a large part of them written in Latin, only four Latin letters have been translated to Lithuanian. This article mostly raises issues rather than provides solutions, since the latter would require more extensive research. The aim is to show the qualities of epistolary texts of the Middle Ages, specifically the Latin correspondence of Vytautas, and the problems of translating them into Lithuanian. The greatest attention is given to a special rhythm (cursus), syllabic strategies at the beginning or at the end of a phrase, the listing of proper names, the selection of epithets or even of conjunctions and their usage, etc. I shall argue that such details could provide plenty of additional information for the analysis of the narrative. Therefore, if they are to be lost in research or translation, it would be a definitive deprivation of full understanding of the medieval rhetoric.